2017
DOI: 10.1111/jtsa.12272
|View full text |Cite
|
Sign up to set email alerts
|

Integer‐Valued Autoregressive Models With Survival Probability Driven By A Stochastic Recurrence Equation

Abstract: This paper proposes a new class of integer‐valued autoregressive models with a dynamic survival probability. The peculiarity of this class of models lies in the specification of the survival probability through a stochastic recurrence equation. The proposed models can effectively capture changing dependence over time and enhance both the in‐sample and out‐of‐sample performance of integer‐valued autoregressive models. This point is illustrated through an empirical application to a real‐time series of crime repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…(13) Table 5 shows the results in terms of point and density forecasting at different horizons h. We note that our model performs well, when compared to the different models proposed in Gorgi (2018), in particular when compared to the GAS-NBINAR model. Overall, we can conclude that the negative-binomial continuous-time Markov process performs well for estimation and forecasting purposes.…”
Section: Application To Crime Datamentioning
confidence: 81%
See 2 more Smart Citations
“…(13) Table 5 shows the results in terms of point and density forecasting at different horizons h. We note that our model performs well, when compared to the different models proposed in Gorgi (2018), in particular when compared to the GAS-NBINAR model. Overall, we can conclude that the negative-binomial continuous-time Markov process performs well for estimation and forecasting purposes.…”
Section: Application To Crime Datamentioning
confidence: 81%
“…This section is devoted to the study of the monthly number of offensive conduct reported in the city of Blacktown, Australia, from January 1995 to December 2014. Following Gorgi (2018), we employ our Gorgi (2018), this indicates over-dispersion, and thus a negative binomial distribution for the error term is a suitable assumption for the data. In Table 4, we compare the estimation values of (r, q, c) and the computational times of our exact transition probability (Exact), Joe's transition probability by computing numerically the integral in Matlab (Numerical Inversion 1) and Joe's transition probability by using an arbitrary precision integral (Numerical Inversion 2).…”
Section: Application To Crime Datamentioning
confidence: 99%
See 1 more Smart Citation
“…BNB–GAS can approximate arbitrarily well some existing models that have been proposed in the literature. As α →∞, BNB–GAS becomes a score‐driven model with negative binomial distribution; see Gorgi (2018) for an application of the GAS framework with negative binomials. As additionally r →∞, the model becomes a Poisson auto‐regressive model, which belongs to the class of models of Davis et al .…”
Section: A Score‐driven Beta–negative Binomial Auto‐regressionmentioning
confidence: 99%
“…Koopman and Lit (2017) used the bivariate Poisson distribution for a number of goals in football matches and the Skellam distribution for a score difference. Gorgi (2018) used the Poisson distribution as well as the negative binomial distribution for offensive conduct reports.…”
Section: Generalized Autoregressive Score Dynamicsmentioning
confidence: 99%